Female ovarian abnormalities and reproductive failure of autumn-spawning herring (Clupea harengus membras) in the Baltic Sea. (8th June 2015) - Ojaveer, Henn; Tomkiewicz, Jonna; Arula, Timo; Klais, Riina
Abstract: Fecundity and reproductive potential are important factors to be considered in evaluating trajectories and demographic predictions of fish populations. Therefore, characterizing the nature and quantifying the extent of any reproductive failure should be considered in fisheries studies. Here, we describe morphological changes in developed ovaries of autumn-spawning herring ( Clupea harengus membras ) caught in the northern Baltic Sea and evaluate the magnitude of this phenomenon during 3 consecutive years. Visibly, abnormal ovaries were histologically characterized by irregular-shaped oocytes in a vitellogenic or final maturation stage with coagulative necrosis and liquefaction of the yolk sphere, degraded follicle membranes, and fibrinous adhesion among oocytes. Such degeneration is presumed to cause complete infertility in the fish. The frequency of fish with abnormal ovaries varied annually between 10 and 15% among all females sampled. However, specific sampling events showed up to 90% females with abnormal gonads. The specific cause of this abnormality remains unknown; however, prevalence was associated with unfavourable environmental conditions encountered before spawning. Thus, ovarian abnormality was positively related to water temperatures, with the highest level found at ≥15°C and negatively related to the frequency of strong winds. The frequency of occurrence of abnormal gonads decreased with the progression of spawning from August to October. The observed abnormality and associated spawning failure will negatively affect the realized fecundity of autumn herring in the Baltic Sea and may act as a limiting factor for recovery of the stock, which has experienced profound depression during the last three decades.